2020
DOI: 10.4103/ijnmr.ijnmr_156_19
|View full text |Cite
|
Sign up to set email alerts
|

The association between moral distress and moral courage in nurses: A cross-sectional study in Iran

Abstract: Background: Moral distress and moral courage among healthcare professionals have received considerable attention in recent years. However, there is a paucity of studies investigating these topics among nurses. Thus, the present study aimed to evaluate the association between moral distress and moral courage among nurses in an Iranian sample population. Materials and Methods: The present cross-sectional study was conducted during February–December 2018. Corley's Moral Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moral courage is a highly valued element of human morality and today an acknowledged virtue in nursing care (Kleemola et al, 2020 ). The available evidence shows that nurses may gain many benefits from using moral courage, including effectively dealing with moral dilemmas (Savel & Munro, 2015 ), resisting the adverse consequences of mental pain (Safarpour et al, 2020 ), reducing the turnover rate of nurses (Rathert et al, 2016 ), thus proving patients with safe and high‐quality care (Numminen et al, 2017 ). If nurses lack moral courage, they will be unable to solve the difficult background factors that prevent them from following moral values (Konings et al, 2022 ) and undermines nurses' integrity as autonomous moral agents (Numminen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moral courage is a highly valued element of human morality and today an acknowledged virtue in nursing care (Kleemola et al, 2020 ). The available evidence shows that nurses may gain many benefits from using moral courage, including effectively dealing with moral dilemmas (Savel & Munro, 2015 ), resisting the adverse consequences of mental pain (Safarpour et al, 2020 ), reducing the turnover rate of nurses (Rathert et al, 2016 ), thus proving patients with safe and high‐quality care (Numminen et al, 2017 ). If nurses lack moral courage, they will be unable to solve the difficult background factors that prevent them from following moral values (Konings et al, 2022 ) and undermines nurses' integrity as autonomous moral agents (Numminen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a study by Aminizadeh et al aimed at determining the relationship between moral courage and moral distress among nurses in intensive care units showed a significant and inverse relationship between the two ( 21 ). Safarpour et al examined the relationship between moral distress and moral courage among Iranian nurses and identified a significant and indirect linear relationship between them; they also found that the severity of moral distress had a significant relationship with gender, but that none of the demographic variables were related to the frequency of moral distress and moral courage ( 22 ). In the present study, there was no statistically significant relationship between working ward, and moral courage and moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are the primary caregivers responsible for upholding the ethics of patient care and are constantly confronted with ethical dilemmas and challenges (1)(2)(3). They serve as ethical agents in ful lling professional commitments, managing ethical situations appropriately, preventing unethical conduct, and strongly advocating for patient-centered care within acceptable standards for patients, their families, and society.…”
Section: Introductionmentioning
confidence: 99%
“…They serve as ethical agents in ful lling professional commitments, managing ethical situations appropriately, preventing unethical conduct, and strongly advocating for patient-centered care within acceptable standards for patients, their families, and society. Therefore, they require ethical courage, which is a worthy characteristic in nurses (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%